(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In the current reform era, the realization of good governance must be supported, among others, by law enforcement against corruption. Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes is the legal basis used in Indonesia. Several cases of judge’s interpretation in a Corruption Case are needed to provide clarity regarding whether or not the elements of a crime have been fulfilled. This thesis discusses "Implementation of Judges’ Interpretation of the Violation of Elements Contrary to the Obligations of Civil Services in Corruption Cases (Case Study of the Corruption Court Decision Number 132 / PID. SUS / TPK / 2017 / PN.JKT.PST." , With the problem and purpose of knowing the forms of legal interpretation in the Corruption Case and the application of the judge’s interpretation to the case study.This research was obtained from primary, secondary and tertiary legal materials which were then analyzed in a descriptive normative manner Analytical interpretation methods and also the construction of law are not permitted in criminal law The Panel of Judges in this case adopted a systematic interpretation in their decision In this case Law Number 31 of 1999 concerns Eradication of Corruption Crimes as amended by Law Number 20 of 2001 concerning Amendment to Law Number 31 of 1999 concerning Corruption Crimes is linked to Act Number 5 of 2014 of the State Civil Apparat us (ASN) concerning Civil Servants.